Prinsip Hidup Kristen di Tengah Masyarakat yang Majemuk - Diana, Ruat; Katarina, K; Tamara, Yesi; Priskila, Kiki (Sekolah Tinggi Teologi Kanaan Nusantara, 2019)
This article discusses the principles of Christian life in a pluralistic society. Indonesia as a country with a pluralistic society has a diversity that can be used to build a nation. Christians in Indonesia have an important role as citizens to realize the progress of the nation. Through the literature research, the author presents the principles of Christian life in a pluralistic society by reviewing various relevant literature. From the results of the study that the authors did, the authors put forward four important principles that need to be done by Christians including 1) building harmony of life, 2) strengthening the faith in the family environment, 3) displaying love as the fruit of the Holy Spirit, 4) understanding the differences that are characteristic of a pluralistic society. Artikel ini membahas tentang prinsip hidup Kristen di tengah masyarakat majemuk. Indonesia sebagai negara dengan masyarakat majemuk memiliki keragaman yang dapat digunakan untuk membangun bangsa. Umat Kristen di Indonesia memiliki peran penting sebagai warga negara untuk mewujudkan kemajuan bangsa. Melalui penelitian pustaka, penulis mengemukakan prinsip hidup Kristen di tengah masyarakat majemuk dengan mengkaji berbagai literatur yang relevan. Dari hasil kajian yang penulis lakukan, penulis mengemukakan empat prinsip penting yang perlu dilakukan oleh orang Kristen antara lain 1) membangun kerukunan hidup, 2) melakukan penguatan iman dalam lingkungan keluarga, 3) menampilkan kasih sebagai buah Roh Kudus, 4) memahami perbedaan yang merupakan ciri dari masyarakat yang majemuk.